Langit putra group bags home best presentation - Putra Science Park, Universiti Putra Malaysia (Putra Science Park, Universiti Putra Malaysia, 2018)
Langit Putra group, consisting of staff from Putra Science Park (PSP) and the Office of the Deputy Vice-Chancellor (Research and Innovation) UPM, emerged victorious in winning the hearts and minds of the jury as it triumphed the best presentation, third place and gold rating awards under the technical category, prevailing over 15 teams from other universities at the 14th Public Universities Creative and Innovative Groups (KIK) Convention, here. The group was made of Asrizam Esam, Norliyana Kamaruddin, Hafliza Hussin, Mohd Mas’Ataillah Ismail, Muhammad Izzat Noradzmi, Norazlin Monir, Mohammad Hisham Omar and facilitated by Shahriman Hashim with its invention the SkytiderTM, a low-cost innovative tool that was designed to help expedite the installation of buntings on tall poles and could be manned by only one person without the need of a ladder. “We mulled over the idea of creating this innovation based on the problems encountered during events or activities that required us to put up or take down outdoor buntings on poles around the campus area. This work was done by our staff since we did not hire any contractors to do it for us. As far as we know, the problems were not only faced by us at UPM but also other universities and the people who run the bunting installation business,”